The market for protection and the origin of the state - Kai A. Konrad; Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2005)
We examine a stark setting in which security or protection can be provided by self-governing groups or by for-profit entrepreneurs (kings, kleptocrats, or mafia dons). Though selfgovernance is best for the population, it faces problems of long-term viability. Typically, in providing security the equilibrium market structure involves competing lords, a condition that leads to a tragedy of coercion: all the savings from the provision of collective protection are dissipated and welfare can be as low as, or even lower than, in the absence of the state.
Keywords: H10; D70; D30; 330; property rights; anarchy; government; Kriminalitätsökonomik; Innere Sicherheit; Sicherheitsgewerbe; Organisierte Kriminalität; Theorie